Getting a grip on the evolution of grasping in musteloid carnivorans: a three‐dimensional analysis of forelimb shape. (11th May 2013) - Fabre, A.‐C.; Cornette, R.; Slater, G.; Argot, C.; Peigné, S.; Goswami, A.; Pouydebat, E.
Abstract: The ability to grasp and manipulate is often considered a hallmark of hominins and associated with the evolution of their bipedal locomotion and tool use. Yet, many other mammals use their forelimbs to grasp and manipulate objects. Previous investigations have suggested that grasping may be derived from digging behaviour, arboreal locomotion or hunting behaviour. Here, we test the arboreal origin of grasping and investigate whether an arboreal lifestyle could confer a greater grasping ability in musteloid carnivorans. Moreover, we investigate the morphological adaptations related to grasping and the differences between arboreal species with different grasping abilities. We predict that if grasping is derived from an arboreal lifestyle, then the anatomical specializations of the forelimb for arboreality must be similar to those involved in grasping. We further predict that arboreal species with a well‐developed manipulation ability will have articulations that facilitate radio‐ulnar rotation. We use ancestral character state reconstructions of lifestyle and grasping ability to understand the evolution of both traits. Finally, we use a surface sliding semi‐landmark approach capable of quantifying the articulations in their full complexity. Our results largely confirm our predictions, demonstrating that musteloids with greater grasping skills differ markedly from others in the shape of their forelimb bones. These analyses further suggest that the evolution of an arboreal lifestyle likely preceded the development of enhanced grasping ability.